Persepsi Pengunjung Terhadap Wisata Bahari Di Pantai Klara, Provinsi Lampung - Nurbaiti Nurbaiti; Sugeng Prayitno Harianto; Dian Iswandaru; Indra Gumay Febryano (Journal of Tropical Marine Science, 2020)
Visitor perception is very important in tourism development because it is one of the indicators that can be used as a reference in tourism management. The purpose of this study was to determine the visitor's perception of the development of marine tourism in Klara Beach, Pesawaran Regency, Lampung Province. Data collection was carried out by the interview method using questionnaires and observation. The collected data were then analyzed using the attraction, accessibility, amenities, and ancillary services with a Likert Scale and a qualitative descriptive. The assessment of visitors' perceptions of attractions, accessibility, and additional services is in a good category. The assessment of visitors' perceptions of facilities is classified as a neutral category, due to limited facilities. Managers are expected to be able to develop tourism optimally by adding facilities needed by visitors, conducting evaluations, and adding tour guides.